Design and fabrication of waste paper recycling machine for laboratory and medium scale operation - Oladele, Isiaka Oluwole; Samuel, Taiwo Anuoluwapo; Adeolu, Adediran Adesoji; Mathew, Omoniyi Ayodeji; Emmanuel, Adanri Oluwafemi (Journal of Production Engineering, 2019)
The current work report the design and fabrication of waste paper recycling machine that is efficient in tackling the challenges of waste paper disposal. The traditional methods of disposing waste papers have proven to be relatively expensive and unhealthy in many developing nations across the globe. Therefore, provision of low technological and cost effective machine for the recycling of these biodegradable wastes in more economical, healthy and safe for the environment is needed. Thus, the objective of this work was to design and fabricate a motorized waste paper recycling machine with slight modifications on the existing ones. The machine was designed to use rotary blades rotated by high speed electric motor followed by performance evaluation of the machine to determine its efficiency. Design calculations were used to ensure cost reliability and minimum energy consumption of the machine. The results showed that 25-30 kg of waste papers per hour were recycled and turned into pulp at a machine speed of 1440 rpm which implies high and good efficiency. The pulp was used for production of waste paper based composite samples with the addition of suitable binders.